1994
DOI: 10.1007/bf00756765
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat induces irreversible actin cytoskeleton disruption in cultured human lung cells

Abstract: The herbicide paraquat (PQ) induces the selective necrosis of type I and type II alveolar pneumocytes. We investigated the effect of PQ on human lung A549 cells to determine the possible role of cytoskeleton in lung cytotoxicity. At 80 mumol/L PQ, a concentration that did not affect cell viability, the organization of actin cytoskeleton network depended on incubation time with the herbicide. Microfilaments appeared less numerous in 30% of the cells treated for 1 h. After 24 h, all the treated cells displayed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The fat body is analogous to the mammalian liver and white adipose tissue, and is implicated in extending lifespan by altered IIS (7). Break-up of the fat body actin cytoskeleton by exposure to paraquat (51) further implies that vital physiological functions (52) are lost. Thus, our results indicate that excess mortality of vg Ϫ bees was linked to cellular damage that included a severe oxidative insult to the fat body.…”
Section: Figmentioning
confidence: 99%
“…The fat body is analogous to the mammalian liver and white adipose tissue, and is implicated in extending lifespan by altered IIS (7). Break-up of the fat body actin cytoskeleton by exposure to paraquat (51) further implies that vital physiological functions (52) are lost. Thus, our results indicate that excess mortality of vg Ϫ bees was linked to cellular damage that included a severe oxidative insult to the fat body.…”
Section: Figmentioning
confidence: 99%
“…Therefore, the discrepancy between our results and their work is probably dependent on the difference in the cells examined. Cappelletti et al [20] also found differences in the cells examined following PQ-induced actin cytoskeleton disruption. On the other hand, we showed that the cells exposed to low levels of NOC18, 20-50 ~tM, improved MTT reduction activity.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, S100A1 may be a molecule that directly links the cytoskeleton and cell growth. The observations that increases in microtubule stability can reverse neuronal cell death associated with Alzheimer's disease (29) as well as neurotoxic agents such as acrylamide and carbon disulfide (30), glutamate (31), and N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (32) suggest that S100A1 may be a suitable pharmacological target for treating neurological disorders. S100A1 antagonists may also be useful agents for the treatment of cancers such as renal carcinoma because these cancers express high levels of S100A1 (see Ref.…”
Section: Discussionmentioning
confidence: 99%